POTENSI IKAN HIAS DI DANAU BATU KABUPATEN PULANG PISAU SUATU PENDEKATAN BIOLOGI DAN ETNOBIOLOGI - Elyta Vivi Yanti; Nicko Haryadi (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2019)
General waters of Central Kalimantan with an area of around 2.29 million Ha is a habitat for freshwater fish, both of which have important economic value and ecological value. Diversity of fish species is a potential for fisheries production both as consumption fish, fish traded between regions and ornamental fish. Based on the latest data, there are 267 species of fish in the public waters of Central Kalimantan and 92 species of which are included in the category of ornamental fish species (Central Kalimantan Marine and Fisheries Service, 2010). Batu Lake is located in Sigi Village, Kahayan Tengah District, Pulang Pisau Regency, Central Kalimantan Province. The area of the lake is approximately 12 km2, around the lake there are rafts and settlements, the distance from the capital city of Kahayan Tengah Subdistrict (bukit rawi + 3 km where the lake slightly enters, through a small road. The distance to the lake is about 250 m from the road) province, the condition of the lake is still natural and only used by residents of Tuwung as a place to find livelihoods (looking for fish and other river products) as well as a means of transportation to certain areas in foodplain waters such as the Lake Batu high water fluctuations (volume of water) in a year is very large. Ruaya fish means adjustment, confidence in conditions that benefit existence and for the reproduction of species with active and sometimes passive movements from one place to another. Effendi (1997) groups the family in the interests of spawning, ruaya to enlargement and food areas and refugee homes to avoid da ri place that is in a bad condition. This research is an effort to introduce the potential of freshwater natural resources in the Lake Batu District of Pulang Pisau in the form of ornamental fish. The inventory activity will provide information about potential types of ornamental fish with all the values of their superiority or attraction so that they can become superior commodities. This research was carried out in Batu Lake (2º 08'23.26